مساهمة في تقييم تجربة الضخ الاستثمارية من طبقة المياه الجوفية المضغوطة في بانياس - شريف بدر حايك (Tishreen University, 2019)
يتضمن البحث دراسة تحليلية لتجربة ضخ استثماري، بهدف تحديد أهم البارامترات، والخصائص الهيدروجيولوجية للطبقة الحاملة للمياه الجوفية المضغوطة في بانياس، وذلك بالضخ من ثلاثة آبار معاً، ولمدة ثلاثة أشهر متواصلة، بمعدلات تصريف تراوح بين  مع قياس تباينات سطح المياه الجوفية في آبار مراقبة مجاورة. اعتمدت طريقة (Cooper-Jacob) المعدّلة؛ لإجراء تقويم تجربة الضخ الاستثمارية، حيث وصلت الناقلية المائية للطبقة الحاملة للمياه إلى 3660 m2/day، وعامل تخزينها 2,86.10-4، ووصل هبوط سطح المياه الجوفية إلى 24m في مركز حقل الضخ، ليتلاشى تقريباً على بعد 1700m، الأمر الذي يتطلب مراقبة ظاهرة اندساس مياه البحر ضمن طبقة المياه الجوفية العذبة. تبلغ مناسيب المياه الجوفية قبل الضخ في مركز حقل آبار الضخ 12m، والميل الهيدروليكي عندها (0,005-0,013)، وتراوح هذه المناسيب بين m(-4, -12) في حقل الضخ بعد الضخ والوصول إلى الجريان المستقر، والميل الهيدروليكي عندها (0,014-0, 1). The research contains an analytical study for an exploitation pumping test. The goal of research is to determine the most important parameters and hydrogeological properties of the confined aquifer in Banyas, by pumping from 3 wells at the same time, this test last for 3 months, and the pumping rates are between (124-160) l/sec. with measuring the fluctuations of the groundwater tables in the neighbor monitoring wells. I adopt the modified method of (Cooper -Jacob, 1964), to evaluate the test, and the transmissivity of the aquifer reaches to 3660,5 m2/day, and the specific storage is 2,86.10-4. And groundwater drawdown is 24m in the center of field pumping wells, to disperse approximately at distance 1700m, so it should be to control of the sea water intrusion into the fresh aquifer. The groundwater levels in the center of well field are 12m before pumping, and the hydraulic gradient is (0,005-0,013). These levels fluctuate between (-4, -12)m in the center of pumping after we get the steady state flow, and the hydraulic gradient is (0,014-0,1).